Protective role of endorepellin in renal developmental programming - Tang, Xiaoshan; Sun, Manqing; Shen, Qian; Rao, Jia; Yang, Xue; Fang, Ye; Xiang, Tianchao; Xue, Shanshan; Sun, Lei; Xu, Hong (Frontiers in Cell and Developmental Biology, 2022)
Adverse intrauterine and early postnatal environment cause reduced nephron endowment and subsequent hypertension, chronic kidney disease (CKD). Exploring modifiable approaches is particularly important to alleviate the global burden of CKD. Enhanced glomerular progenitor cells apoptosis is a major contributor to the renal developmental programming. The differentially expressed protein perlecan, which we previously identified by proteomics, is an important extracellular matrix glycoprotein, and its domain V (endorepellin) can inhibit apoptosis through a paracrine form. In explanted mice embryonic methanephros, we found that endorepellin can rescue glomeruli deficit phenotype result from malnutrition, and this protective effect was also verified in vivo renal developmental programming model which be given low protein diet during pregnancy. We further demonstrated that endorepellin significantly inhibited glomerular progenitor cell apoptosis via activates ERK1/2 phosphorylation. Our results show that endorepellin rescues the nephron number reduction in renal developmental programming, possibly through the inhibition of progenitor cell apoptosis via ERK1/2 pathway.